2012
DOI: 10.5114/jcb.2012.27950
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo dosimetric study of the Flexisource Co-60 high dose rate source

Abstract: PurposeRecently, a new HDR 60Co brachytherapy source, Flexisource Co-60, has been developed (Nucletron B.V. Veenendaal, The Netherlands). This study aims to obtain dosimetric data for this source for its use in clinical practice as required by AAPM and ESTRO.Material and methodsTwo Monte Carlo radiation transport codes were used: Penelope2008 and GEANT4. The source was centrally-positioned in a 100 cm radius water phantom. Absorbed dose and collisional kerma were obtained using 0.01 cm (close) and 0.1 cm (far)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…The density of water considered is 0.998 g/cm 3 at 22°C [1]. In order to provide adequate spatial resolution, the cells are 0.01 cm thickness for r < 2 cm, 0.05 cm for 2 < r < 5 cm, 0.1 cm for 5 < r < 10 cm and 0.2 cm for r > 10 cm from the source [2, 10]. The dose rate values are calculated in different positions of the water phantom with polar and Cartesian co-ordinates for different position of the water phantom.…”
Section: Methodsmentioning
confidence: 99%
“…The density of water considered is 0.998 g/cm 3 at 22°C [1]. In order to provide adequate spatial resolution, the cells are 0.01 cm thickness for r < 2 cm, 0.05 cm for 2 < r < 5 cm, 0.1 cm for 5 < r < 10 cm and 0.2 cm for r > 10 cm from the source [2, 10]. The dose rate values are calculated in different positions of the water phantom with polar and Cartesian co-ordinates for different position of the water phantom.…”
Section: Methodsmentioning
confidence: 99%
“…The relatively small differences in the radial dose distribution of 60 Co sources compared to 192 Ir sources 5,6 do not result in clinically significant effects. 1,2,4,5,7,8 Different companies provide 60 Co HDR brachytherapy sources [9][10][11][12] and at least 200 remote afterloader systems equipped with 60 Co are presently in operation worldwide. 3 The dosimetric verification of a 60 Co brachytherapy source in a hospital using an in-air experimental set-up is complex and time-consuming [13][14][15][16][17] and may be error-prone, among other things, due to lack of guidelines for 60 Co sources in the existing dosimetry protocols.…”
Section: Introductionmentioning
confidence: 99%
“…(2012) used the MCNP4C Monte Carlo code to obtain the dosimetric parameters of GZP6 60 Co sources. However, in the study of Vijande et al ,. it is indicated that the radial dose function from the study of Tabrizi et al.…”
Section: Introductionmentioning
confidence: 91%
“…This work comprises a full and MC‐based dosimetry report for GZP6 60 Co source number 3 according to the recommendations of the American Association of Physicists in Medicine (AAPM) and the European Society for Radiotherapy and Oncology (ESTRO) on dose calculations for high‐energy (average energy higher than 50 keV) photon‐emitting brachytherapy sources . The calculated dosimetric parameters were compared with the available data of the similar 60 Co high dose rate (HDR) sources and the detailed dosimetric characterization of GZP6 60 Co source number 3 was discussed.…”
Section: Introductionmentioning
confidence: 99%